Echo‐planar imaging of the human head with 100 mT/m gradients and high‐order modeling of eddy current fields. Issue 2 (21st January 2020) - Hennel, Franciszek; Wilm, Bertram; Roesler, Manuela B.; Weiger, Markus; Dietrich, Benjamin; Pruessmann, Klaas P.
Abstract : Purpose: To demonstrate the utility of a high‐performance gradient insert for ultrafast MRI of the human head. Methods: EPI was used for the first time with a readout gradient amplitude of 100 mT/m, 1200 T/m/s slew rate, and nearly 1 MHz signal bandwidth for human head scanning. To avoid artefacts due to eddy currents, the magnetic field was dynamically monitored with NMR probes at multiple points, modeled by solid harmonics up to fifth order, and included in the image reconstruction. An approximation of a negligible intra‐echo effect of the eddy currents was made to accelerate the high‐order reconstruction. The field monitoring‐based approach was compared with a recently proposed phase error estimation from separate reconstructions of even and odd echoes. Results: Images obtained with the gradient insert have significantly lower distortions than it is the case with the whole body 30 mT/m, 200 T/m/s gradients of the same system. However, eddy currents of high spatial order must be properly characterized and corrected for in order to avoid a persistent 2D Nyquist ghost. Multi‐position monitoring proves to be a robust method to measure the eddy currents and allows higher undersampling rates than the image‐based approach. The proposed approximation of the eddy currents effect allows a significant acceleration of the high‐order reconstruction by a separate processing of each spatial dimension. Conclusion: Strong gradients with adequate switching rates are highly beneficial for the quality of EPI provided that robust measures are taken to include the contribution of eddy currents to the image encoding.